GROWTH AND REPRODUCTIVE POTENTIAL OF GUPPY POECILIA RETICULATA (PETERS) IN MODULAR SYSTEM OF FISH PRODUCTION - Manikandavelu, D; Neethiselvan, N (Indian Journal of Fisheries, 2011)
By increasing the growing space at periodic intervals, the growth and reproductive potential of thecommon aquarium fish guppy has been monitored over a period of 84 days. When the animals havebeen transferred from one module with less living space to another with larger space, there is a substantialincrement both in size and reproductive capacity. By having such a modular system of fish production,we can have a continuous harvest instead of constantly growing them in a larger space to get larger andmore number of animals. The sex ratio of males to females in this system appears to be around 2 : 5.